Tratamiento multidisciplinario mínimamente invasivo de la sonrisa gingival - Domínguez Díaz, Deysi Desirée (2020)
The increasing demand of patients for esthetics dentistry treatments has led to the development of multidisciplinary communication between approaches among different specialties to achieve treatment success. The gummy smile is a frequent esthetic problem, which consists of excessive exposure of the gum when smiling. Treatment modalities range from gingivectomy to flap lift for the removal of excess bone. Restoration with direct veneers of composite resins is suitable for the preservation and esthetic improvement of the anterior sector, with optimal aesthetics and durability. In addition, minimally invasive treatment can be considered due to its conservative concepts of preserving the dental structure. The present case describes the treatment of a young patient with gummy smile and alteration in shape and color of the anterior teeth, through minimally invasive procedures such as gingivectomy and rehabilitation with direct veneers of composite resins with the objective of preserving the dental structure and greater esthetic - functional predictability. The present case report describes the treatment of a young patient with gummy smile. The shape and color of the anterior teeth were altered by minimally invasive procedures including gingivectomy and rehabilitation with direct veneers of composite resins with the objective of preserving the dental structure and providing greater esthetic - functional predictability.